Maktablarda ma‘naviy-ma‘rifiy ishlar tizimiga ekologik targʻibot-tashviqot ishlarini tashkil etish (SCIENCE and SOCIETY, 2023)
This article discusses the organization of environmental propaganda and agitation work in the system of spiritual and educational work carried out in educational institutions, that is, it talks about carrying out activities to attract schoolchildren to environmental work.